2019
DOI: 10.1038/s41598-019-47821-1
|View full text |Cite
|
Sign up to set email alerts
|

Evidence for tritium persistence as organically bound forms in river sediments since the past nuclear weapon tests

Abstract: Tritium of artificial origin was initially introduced to the environment from the global atmospheric fallout after nuclear weapons tests. Its level was increased in rainwaters by a factor 1000 during peak emissions in 1963 within the whole northern hemisphere. Here we demonstrate that tritium from global atmospheric fallout stored in sedimentary reservoir for decades as organically bound forms in recalcitrant organic matter while tritium released by nuclear industries in rivers escape from such storages. Addit… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
8
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 14 publications
(10 citation statements)
references
References 39 publications
(54 reference statements)
0
8
0
Order By: Relevance
“…Still, it is unclear why the 3 He would adhere to the oily residue. Previous work has shown that bomb tritium can be organically bound (Eyrolle et al., 2019) but whether organics would host tritium in the biologically poor South Pole environment, and whether organic molecules can retain 3 He, are open questions. Note that production of 3 He by the beta decay of tritium‐rich fallout would not affect the vast majority of the core samples, most of which were deposited before the atomic era.…”
Section: Resultsmentioning
confidence: 99%
“…Still, it is unclear why the 3 He would adhere to the oily residue. Previous work has shown that bomb tritium can be organically bound (Eyrolle et al., 2019) but whether organics would host tritium in the biologically poor South Pole environment, and whether organic molecules can retain 3 He, are open questions. Note that production of 3 He by the beta decay of tritium‐rich fallout would not affect the vast majority of the core samples, most of which were deposited before the atomic era.…”
Section: Resultsmentioning
confidence: 99%
“…It is important to note that in the case of fluvial environments, the sedimentation rate is variable over time contrary to lakes and quiet environments. Consequently, the 210 Pb xs dating method is not available in this study as previously mentioned in Grosbois et al (2012), Eyrolle et al (2019), Morereau (2020) and Copard et al (2021). Hence, these identified chronological landmarks (1963, 1969, 1980 and 1986) allow obtaining a robust age model presenting two main periods with constant sedimentation rates, the 1963 -1986 period with 2.4 ± 0.2 cm/y and the 1986 -2016 period with 1.3 ± 0.2 cm/y with uncertainties estimated to ± 2 years.…”
Section: Methodsmentioning
confidence: 99%
“…In 1969 and 1980, two nuclear accidents took place at the former Saint-Laurent-des-Eaux NPP (NUGG reactors named SLA1 and SLA2 respectively). These events led to the fusion of fuel elements and plutonium was detected in water and sediment in the Loire River (Eyrolle et al, 2019;Guignard and Catoire, 2015;IRSN, 2016;Thomas, 1982). All NUGG reactors located on the Loire watershed were definitely stopped in 1992.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…(1) The chemical component carrying 3 H may also be the cause of increasing δ 2/1 H. This carrier could be methane formed by degradation of organic matter in an environment where tritium may reach high values, such as sediments rich in organic matter that acquired a high tritium concentration at the time of atomic weapon experiments. For instance, Eyrolle et al [98] reported high tritium concentrations in the organic portion of the sediments from the Loire River in Western France.…”
Section: Hydrogeological Modelmentioning
confidence: 99%